Research of neutron interaction with matter under high neutron flux. Part III. Research of neutrons transmission time dependence - Yu. G. Shchepkin; V. I. Slisenko; N. I. Мazina; Т. O. Коstyuk (Ядерна фізика та енергетика)
Measurements of the transmission of neutrons through two samples of 235U and Cd, which are simultaneously on neutron beam, with different sequence of their location for different exposure times of the samples on the beam, are performed. Previously observed difference in these transmissions is confirmed – asymmetry of transmission. The purpose of the measurements is to determine the lifetime of the expected metastable states, to explain the observed asymmetry of transmission. Based on the results of asymmetry of transmission measurements, it was found that it is less than 5 s.